Deindustrialization and the Polarization of Household Incomes: The Example of Urban Agglomerations in Germany - Martin Gornig; Jan Goebel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The tertiarization, or perhaps more accurately, the deindustrialization of the economy has left deep scars on cities. It is evident not only in the industrial wastelands and empty factory buildings scattered throughout the urban landscape, but also in the income and social structures of cities. Industrialization, collective wage setting and the welfare state led to a stark reduction in income differences over the course of the twentieth century. Conversely, deindustrialization and the shift to tertiary sectors could result in increasing wage differentiation. Moreover, numerous studies on global cities, the dual city, and divided cities have also identified income polarization as a central phenomenon in the development of major cities. Using data from the German Socio-Economic Panel (SOEP), we find an increasing polarization of household income structures since the mid-1990. In agglomerations, this income polarization is even more pronounced than in the more rural regions. The income polarization in Germany is likely to have multiple causes, some of which are directly linked to policies such as the deregulation of the labor market. But extensive deindustrialization is probably also one of the drivers, that has led directly to the weakening of middle income groups.
Keywords: R20; Z13; R11; 330